Hydrochemical assessment of groundwater for drinking and irrigation suitability in Vaniyambadi region, Tamil Nadu, Southern India: A sustainable approach - Ramachandran A; Richard Abishek S; Stephen Pitchaimani V; Suresh Gandhi M; Prakash V (Cleaner Water, 2025)
This study assesses groundwater quality in the Vaniyambadi region of southern India, examining its suitability for drinking and irrigation purposes. Groundwater samples were analyzed for physicochemical parameters, major ions, and heavy metals and the results were compared with WHO (2017) standards. Results show slightly alkaline conditions (pH 7.4–8.4), and 88 % of samples exceeding recommended TDS levels (460–2220 mg/L), indicating salinity issues from natural mineral dissolution and human activities like agricultural runoff. The calcium, magnesium, and bicarbonate levels are within the limit guidelines, while heavy metal concentrations - particularly chromium (0.26 mg/L), nickel (0.18 mg/L), cadmium (0.025 mg/L), and lead (0.17 mg/L) - surpass safe limits, suggesting industrial contamination risks. The Water Quality Index classified 68 % of samples as ''Excellent'' or ''Good'' for drinking, 32 % ''Poor'' or ''Very Poor'' categories due to salinity and contamination. Irrigation suitability analysis reveals 60 % of samples have favourable sodium levels, while 40 % may pose sodium-related risks to soils. Hydrochemical characterization identifies carbonate weathering and rock-water interactions as primary influences, with some evaporation effects. These findings highlight the necessity for improved pollution controls, sustainable water management practices, and ongoing quality monitoring to protect this vital resource. The study offers essential data to developing targeted groundwater protection strategies in the region.